Moving toward a common goal via cross-sector collaboration: lessons learned from SARS to COVID-19 in Singapore - Soojin Kim; Yuki Goh; Jun Hong Brandon Kang (BMC, 2022)
Abstract Background The spread of COVID-19 has taken a toll on many countries and its healthcare system over the last two years. Governments have sought to mitigate the repercussions of the pandemic by implementing aggressive top-down control measures and introducing immense fiscal spending. Singapore is no exception to this trend. Owing to a whole-of-society approach, Singapore is still being lauded globally for its relatively successful record at controlling both community and trans-border spread. One notable effort by the Singapore government has taken place through its cross-sectoral collaborative partnerships with the private stakeholders behind the success. Methods/results In an attempt to better explain Singapore's robust yet strategic response to COVID-19, this study focuses on how the experience of the SARS outbreak has informed the government's collaborative efforts with other stakeholders in society, beyond mere transnational cooperation. Taking a comparative case study approach in the specific context of Singapore, we perform a content analysis of related government documents, mainstream newspaper articles, and academic journal articles in an inductive manner. By closely comparing two global healthcare outbreaks, we note four differences in approach. First, during the COVID-19 pandemic, Singapore has focused on securing sufficient essential healthcare resources with contingency plans to strengthen preparedness. Second, the government has actively harnessed the capacity of private entities to promote the resilience of the healthcare system and the community. Third, Singapore's management policies have been made not only in a top-down, centralized style during the initial response stage, but also with a greater proportion of bottom-up approaches, particularly as the pandemic trudges on. More interestingly, the multi-faceted repercussions of COVID-19 have gradually opened the door to a greater variety of collaborative partnerships in sectors beyond healthcare services. The participating stakeholders include, but are not limited to, local and international business actors, non-profit organizations, academia and other countries. Lastly, as the pandemic has continued, the Singapore government has managed outward to tap the expertise and knowledge of the private sector, in particular leveraging science and technology to improve control measures and putting supportive programs into practice. Conclusion The evidence from our focused analyses demonstrates that the nature and scale of the COVID-19 pandemic produced more collaborative partnerships between the public and private sectors in Singapore as compared with the SARS outbreak. What is more, our findings offer evidence that through adaptive learning from the prior global healthcare outbreak, plus some trial and error during the initial phase of the ongoing pandemic, public- and private-sector partners, both in and outside of the healthcare service sector, have tended to "act alike," working together to achieve a common goal. Both have been socially responsible, providing public services to people in need to promote the rapid resilience of the community, and sharing the associated risks. Overall, this study has deep and wide implications for other governments and policy makers who are still struggling to maximize essential resources and minimize the negative impacts of the healthcare crisis.